Astrobiology from early-career scientists' perspective. Issue 4 (October 2015) - Noack, Lena; Verseux, Cyprien; Serrano, Paloma; Musilova, Michaela; Nauny, Philippe; Samuels, Toby; Schwendner, Petra; Simoncini, Eugenio; Stevens, Adam
Abstract What is astrobiology? Which fields does it comprise and what makes an astrobiologist? Ask five scientists and you may end up with six different definitions. This issue was raised at the first symposium of the European network of Astrobiology Graduates (AbGradE), held last year in Edinburgh, when discussing whether the attendees' fields of study were represented in the astrobiology community.